Exploring the evidence for conservation-poverty link: the case of Kg. Tudan, Kiulu, Tuaran, Sabah. - Abdul Aziz, Nor Akmar; Saikim, Fiffy Hanisdah; Jetony, Jerald; Pengiran Bagul, Awangku Hassanal Bahar; Suleiman, Monica; Mohd. Nordin, Nordiana; Hamzah, Zulhazman (Forestry Department of Peninsular Malaysia, 2021)
Kg Tudan, a village with steep terrain and infertile soils located within the buffer area of Crocker Range Biosphere Reserve (CRBR) is requiring policy and socio-economic interventions. Universiti Malaysia Sabah (UMS), through some funding from the Federal Government, has implemented the Knowledge Transfer Programme (KTP) and MOSTI Social Innovation (MSI) for alternative uses of the mulberry products. The main objective of this study is to identify the missing links between biodiversity conservation and poverty alleviation. The study also identified factors that motivate the community's participation in the livelihood enhancement program coordinated through the KTP and MSI programs as well as the impacts of such programs on the protection of natural resources in Crocker Range Park. A qualitative interview of 35 respondents was conducted in Kg. Tudan, Kiulu, Tuaran. Based on the content analysis using Leximancer, the results revealed that the primary motivation of their participation is financial support, community enhancement through training program and certification, enhancement of facilities, the opportunity for employment, and cultural recognition. Findings also unearthed that only 3% of the respondents are still going to the forest to extract natural resources after implementing poverty alleviation projects. The findings can be deduced that social value is substantial in local community participation in poverty alleviation projects. Therefore, the study's outcome is crucial as preliminary discoveries of moving beyond the "conservation-poverty" debate towards on-the-ground implementation. Thus, contributing to addressing the knowledge gaps between biodiversity conservation and poverty alleviation of local communities.